Histórias de vida de mulheres empreendedoras em Foz do Iguaçu - Ludwig, Alessandra Leite Prado (2017)
The life histories of executive women of outstanding economic success in the city of Foz do Iguaçu were challenged, aiming, in a general way, to evaluate elements of tension between the collective and the individual female from the contexts of career and family, supporting On the tripod of the thesis of economic emancipation, allied to the development of an active subjectivity and reinforced by coping practices. The entrepreneurial executive woman was analyzed; One that performs complex administrative activities with responsibility; The one that occupies position of command and political and technical knowledge of the business performed and how it reconciles this sphere of public control with the domestic relations. The methodology that guided the investigation was the History of Life, which makes it possible to raise elements of collateral experience in the formation of history, that is, an active and influential cultural meaning from individual representations: stories that reconstruct collective history from the perspective of experiences Lived. Among the bibliographic bases are: Lewin (1980) Feminine education and workforce in Brazil, Jonathan e Silva (2006) Feminist entrepreneurship: weaving the plot of conflicting demands, Pinsky (2009) Gender studies and Social History, highlighting gender as a category of language analysis and deconstruction of power relations in Scott (1986, 1987, 1988, 1990, 1992), Cyrino (2012) Executive Women, Institute of Applied Economic Research - IPEA (2010) Geertz (2008) The interpretation of cultures, Velho (2008) Individualism and Culture, Piscitelli (1993) Oral Tradition, Memory and Gender. We worked in an interdisciplinary universe of research, exploring concepts that integrate exact and human areas to end in the context of the entrepreneurial culture and the peculiar formation of the symbols of gender, as they operate in daily and current practice. We questioned women of outstanding success, identifying in their trajectories continuities and symbolic discontinuities,for the diagnosis of forms of cultural re-signification.